Interests, Institutions, and Information : Domestic Politics and International Relations - Milner, Helen V., 1958- (Book collections on Project MUSE., 1997)
Interests, Institutions, and Information examines the central factors that influence the strategic game of domestic politics. It shows that it is the outcome of this internal game - not fears of other countries' relative gains or the likelihood of cheating - that ultimately shapes how the international game is played out and therefore the extent of cooperative endeavors. The interaction of the domestic actors' preferences, given their political institutions and levels of information, defines when international cooperation is possible and what its terms will be. Several test cases examine how this argument explains the phases of a cooperative attempt: the initiation, the negotiations at the international level, and the eventual domestic ratification. The book reaches the surprising conclusion that theorists - neo-Institutionalists and Realists alike - have overestimated the likelihood of cooperation among states.